Nutritional status in critical patients as a predictor of morbidity and mortality in a National Hospital of Essalud in Lima-Peru - Roque Aycachi, Jossiel (2019)
Objetive: The objective was to determine the association of morbidity and mortality in the nutritional status ofpatients admitted to the Special Care Unit (SCU) Emergency of Hospital Nacional Guillermo Almenara Irigoyen.Methods: The study is not experimental design, slitting, powerful analytical observational retrospective cohort.The sampling was non probabilistic for convenience. The group was formed by 124 patients, who were dividedinto two groups, malnourished (n = 31) and normally nourished (n = 93) for the observation of both groups fromexposure (mechanical ventilation, infection, hospital stay, discharge status). Results: Was found a significantrelationship and an odds ratio between nutritional status and mechanical ventilation (OR = 2.6; p <0.033),infections (OR = 2.6; p <0.038), hospital stay (OR = 4.154; p <0.01) and discharge status (OR = 3.646; p <0.004).Conclusions: Finally, we reach the conclusion of a significant relationship between the studied variables.